`Some People Drink as the Body Should Feel a Little Ease': Understanding Body Management amongst Manual Labourers in Western India - Louise Waite (JOURNAL OF SOUTH ASIAN DEVELOPMENT 2007; 2; 227, 2007)
Despite development studies' core concern with vulnerable bodies, the discipline has been somewhat sluggish in embracing the expansive and fruitful literature around embodiment. One aspect of this terrain is `body management'; a topic often discussed in contexts of Western consumerism where the body is perceived as a malleable entity subject to transformation. This article discusses a group of manual labourers in India who are not reflexively reconstituting themselves through post-modern playfulness, but whose fleshy bodies are nevertheless of pivotal importance in their labour-intensive livelihoods. It is this understanding of bodies as primary assets in the lives of the working poor that begs a deeper understanding of how bodies are managed within realms that ostensibly appear to harm the embodied condition of labourers. This article explores subtle and embedded body management strategies, and also asks if there are limits to the notion of a selfdirected project of benevolent body management.